2010
DOI: 10.1007/s10404-010-0753-6
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of fluidic chips with 1-D nanochannels on PMMA substrates by photoresist-free UV-lithography and UV-assisted low-temperature bonding

Abstract: A novel method for fabricating nano-or submicro-fluidic PMMA chips using photoresist-free UVlithography and UV-assisted low-temperature bonding was developed. The nano-or submicro-channels were fabricated by exposing the PMMA substrate to the UV-light through a mask for a certain time. The PMMA substrate with channels and another flat PMMA cover sheet were pretreated with the UV-light for 2 h before they were brought together in running water. The bonding was carried out under a pressure of (1.19 ± 0.12) 9 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Meanwhile, an increasing number of unconventional fabrication techniques have also been developed in recent years 19 . For example, some polymers, such as polycarbonate 20,21 and polymethylmethacrylate (PMMA) 22 , have desirable material properties, whereby they can decompose and form nanoscale structures on the surfaces when they are exposed to UV light or treated in a thermal compression process 23 . Although these methods provide alternative solutions for nanofabrication that are typically simple and low-cost, they show limitations in terms of the fabrication success rate and throughput, and they have insufficient control of the geometric dimensions for the fabricated nanochannels.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, an increasing number of unconventional fabrication techniques have also been developed in recent years 19 . For example, some polymers, such as polycarbonate 20,21 and polymethylmethacrylate (PMMA) 22 , have desirable material properties, whereby they can decompose and form nanoscale structures on the surfaces when they are exposed to UV light or treated in a thermal compression process 23 . Although these methods provide alternative solutions for nanofabrication that are typically simple and low-cost, they show limitations in terms of the fabrication success rate and throughput, and they have insufficient control of the geometric dimensions for the fabricated nanochannels.…”
Section: Introductionmentioning
confidence: 99%
“…The metalization of polymer surface are of great interest due to their numerous potential applications in fields such as surface protection [1], microelectronics industry [2], surface decoration [3], and the fabrication of biological devices [4]. Several experimental studies for preparing the metallized polymer were reported including magnetron sputtering deposition [5], electroplate [6], or electroless plating [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental studies for preparing the metallized polymer were reported including magnetron sputtering deposition [5], electroplate [6], or electroless plating [1][2][3][4]. Electroless plating is particularly attractive among these methods due to its less requirement for expensive facilities, less restriction in surface topography, low cost, and reliable capability for large area deposition [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, polymer instead of silicon or quartz is often considered as a better choice for making microfluidic devices (Song and Lee 2006). Several groups have been using PDMS and other polymers to fabricate micro and nanofluidic channels (Lei Zhang et al 2008;Xianqiao Hu et al 2011), often nanometer dimensions are obtained but accurate shape control at the sub micron level is not easy to achieve. Other groups have used alternative materials to replicate nanofluidic channels (Rolland et al 2004;De Marco et al 2008).…”
Section: Introductionmentioning
confidence: 99%